Determination and Pharmacokinetics of Okanin in Rat Plasma by UltraHigh Performance Liquid Chromatography Coupled with Triple-Quadrupole Tandem Mass Spectrometry. (28th August 2020) - Shi, Yurui; Chen, Rongda; Xie, Jing; Li, Li; Liu, Guiming; Zheng, Meizhu; Zhang, Ning
Abstract : Okanin is a major flavonoid found in Coreopsis tinctoria Nutt., arousing huge interest recently for its considerable biological characteristics including antioxidant, antineurotoxic, and antidiabetic activities. An ultrahigh performance liquid chromatography triple-quadrupole tandem mass spectrometry (UPLC-MS) was successfully used to determine okanin in rat plasma after oral administration of okanin. Bavachalcone acted as an internal standard (IS). By gradient elution, IS and analyte were separated on a C18 column for 7 min at a flow rate of 0.25 mL/min with acetonitrile-0.1% acetic acid mobile phase. The stability, matrix effect, extraction recovery, accuracy, precision, linearity, and selectivity of the method were firstly demonstrated. The major pharmacokinetic parameters of okanin in rat plasma were then measured using the developed UPLC-MS method. An UPLC-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) was finally established to obtain the specific and accurate mass of okanin in rat plasma after oral administration, and its proposed fragmentation was further elaborated.